KESULITAN BELAJAR DAN FAKTOR PENYEBABNYA PADA SISWA SMP SABILAL AKHYAR KWALA GUMIT - Nurhasanah, Nurhasanah; Satriyadi, Satriyadi (Institut Syekh Abdul Halim Hasan Binjai, 2022)
Learning difficulties are a condition of students facing certain obstacles in taking the educational process and achieving maximum learning outcomes. This study aims to determine the learning difficulties faced by students and to find out the causes of students experiencing difficulties in learning. The method used in this research is a survey method, where we give several questionnaires or questions to students about learning difficulties. The sample in this study was 100 students at SMP Sabilal Akhyar Kwala Gumit. The results showed that the students' learning difficulties were communal or collective difficulties felt by some students